(untitled) (Tempo e Argumento, 2021)
This paper exams how Brazilian civil-military dictatorship period is taught at Brazilian basic education. It is based on the analysis of 18 final projects` history teachers wrote to achieve their masters’ degrees, between 2014 and 2019. This master is part of the program "Professional Master in History Teaching - ProfHistória." The analysis considers two premises: first, current events affect the way teachers and students articulate their understanding in history classes; second, reflection on political and ethical principles affects deeply the writing and teaching of history nowadays. Considering specific parts of final projects, this paper analyzes the meaning teachers employ regarding the teaching of civil-military dictatorship history. It explores the political context marked by the effects of State policies of memories and the strengthening of narratives that justify or deny the dictatorship, as well as political crisis that marked those years. Teachers’ reflections and proposals defend history in basic education as a potential tool to develop abilities such as the understanding of social production and conflicts between different memories concerning dictatorial past. It also can help students to criticize narratives that denies or justifies dictatorship today. The activities produced by teachers are based in varied didactic sources and academical History methodologies and aim to engage students in teaching-learning process. Teachers also conceives the teaching of civil-military dictatorship history in basic education as a social commitment to reinforce support to democratic regime among students. Keywords: History teaching; civil-military dictatorship; Professional Master in History Teaching – ProfHistória.